Numerical Study on the Effect of Glazing Layer on the Performance of a Flat Plate Solar Collector - Akeef Mursyidiy; Syed Noh Syed Abu Bakar; Mohammad Jamil Ahmad; Mohd Azan Mohammed Sapardi; Sany Izan Ihsan (International Journal of Integrated Engineering, 2026)
The glazing or glass cover is a key component of a flat plate solar collector (FPSC), influencing both thermal and optical performance. This study investigates the effect of varying the number of glazing layers (1 to 4) on the absorber plate temperature and top heat loss coefficient. Results show that the 2-glazing layer configuration yields the highest absorber temperature at 376.48?K, but also a relatively higher top heat loss coefficient, Ut, compared to the 3 and 4-glazing layer configurations. The top heat loss coefficient shows a diminishing decline as more glazing layers are added. Adding glazing layers introduces a greenhouse effect by transmitting solar short-wave radiation while trapping long-wave heat, which enhances FPSC thermal retention but slightly reduces surface incident radiation due to optical losses. The 2-glazing configuration yields the highest absorber temperature due to its balance between Ut and surface incident radiation. These findings provide insight for optimizing glazing configurations in solar collector design.